Design a mixer for grain materials - Khairul Aswad Mohammed Soffi (Universiti Malaysia Perlis, 2008)
Plastics extrusion is a high volume manufacturing process in which raw plastic material is melted and formed into a continuous profile. Extrusion produces items such as pipe or tubing, weather stripping, window frames, plastic sheeting, adhesive tape and wire insulation. Mixer or dosing unit is one of equipment extruder line, which is function to mix material before it is extruded by screw of extruder. Four kind of materials is mixed by mixer becomes homogeneous. Material is plastic grain materials. Control system is used to control absorption of five kinds of materials. This process of mixing the material is for creating polymer. A polymer is a substance composed of molecules with large molecular mass composed of repeating structural units, or monomers, connected by covalent chemical bonds. Well known examples of polymers include plastics, DNA and proteins. For my project, I need to design a custom made hopper that not only receive pallet but also mixing it. After that I need to proof that this system can produce mixed commodity plastic material to creating plastic polymer. Commodity plastics are plastics that are used in high volume and wide range of applications, such as film for packaging, photographic and magnetic tape, beverage and trash containers and a variety of house hold products where mechanical properties and service environments are not critical. Such plastics exhibit relatively low mechanical properties and of low cost.